Trabalho acadêmico e saúde de estudantes de pós-graduação diante dos cortes de financiamento à pesquisa - Reis, Ana Carolina (2022)
Considering the gradual reduction in the promotion of Science and Technology (S&T) in recent years, and paying attention to the situations in which postgraduate researchers find themselves, the general objective of the research is to investigate the reverberations of the current Science Financing policies and technology in academic work and in the health of postgraduate research students. For this, the research analyzed science and technology funding policies at the federal level in the last 5 years, evidencing the conception of State in which these policies are modeled; It analyzed the possible influences of funding policies and their demands on the postgraduate organization, mapping possible psychosocial risks and, finally, investigating other possible variables that are subject to relative changes and courts in funding policies and that may exert influences . in mental health, assigning meaning to academic work and ways of organizing graduate work. The study demonstrates its relevance in light of the need for reflective theoretical deepening on the dynamic relationships between the capital crisis, the new forms of socialization and subjectivity present in academic everyday life, as well as the attributions of functions in relation to public universities in this context, in order to teach new regulations. The methodology for obtaining two results was used from the triangulation of document analysis, questionnaires and semi-structured interviews. The collection of two data was carried out at the National Institute for Space Research (INPE), in view of the current situation of the institution. The study sample included students from four graduate programs. In theoretical terms of analysis of two results, an investigation based on the assumptions of Psychodynamics of Work was privileged, in an interdisciplinary perspective with the other Clinics of Work, Sociology of Education and Sociology of Work. The results suggest dissatisfaction with funding policies, given that this item greatly interferes with students' daily work. The results also suggest an increase in demands and overload, showing the intensification and extension of working hours for postgraduates, weakening the university-private life reconciliation, so that work becomes their own activity. This research favors discourses on two impacts of non-daily financial factors on students, exacerbated self-demand and lack of support that emerged from the managerial mentality. We identified that the levels of satisfaction after entering graduate school decreased, which allows us to infer that the relationship between work management and disciplines tends to produce weaknesses in the students' experiences. The confluence of the two interviewees' answers demonstrates, in addition to individualizing perceptions and symptoms, a collective demonstration of pathologizing ways of life that we have in tune with the work carried out.